2003
DOI: 10.1038/sj.bmt.1704166
|View full text |Cite
|
Sign up to set email alerts
|

Regimen-related toxicity after fludarabine–melphalan conditioning: a prospective study of 31 patients with hematologic malignancies

Abstract: Summary:A total of 31 consecutive patients with hematologic malignancies who were considered poor candidates for TBI underwent allogeneic stem cell transplantation after conditioning with fludarabine and melphalan. A total of 25 matched sibling recipients received fludarabine 25 mg/ m 2  5 days and melphalan 70 mg/m 2  2 days. For unrelated and haploidentical donor recipients, fludarabine was increased to 30 mg/m 2 and ATG 30 mg/kg  4 days was added. Graft-versus-host disease prophylaxis consisted of tacrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 29 publications
1
29
2
Order By: Relevance
“…1,23,24 In addition, our series reports no cases of VOD. This observation is in contrast to previous studies where, although the incidence and severity was less than in full intensity regimens, morbidity 25 and mortality 26 from VOD were still reported.…”
Section: Discussioncontrasting
confidence: 55%
“…1,23,24 In addition, our series reports no cases of VOD. This observation is in contrast to previous studies where, although the incidence and severity was less than in full intensity regimens, morbidity 25 and mortality 26 from VOD were still reported.…”
Section: Discussioncontrasting
confidence: 55%
“…68 Surprisingly, after an initial report 59 of about 2.5% incidence of grade IV/V cardiac toxicity with this combination, this unexpected side effect has been confirmed in three other reports, with incidence up to 14% and outcomes variable from complete reversibility with standard medical treatment 69 to toxic deaths. 70,71 These data clearly contrast with the reported rarity of cardiotoxicity with either agent individually. The mechanism of this unique toxicity is not known, as none of the patients had a history of cardiac disease and all of them had normal pre-transplant cardiac function and limited, if any, previous exposure to anthracyclines.…”
Section: Other Chemotherapeutic Agentscontrasting
confidence: 56%
“…Some authors have found that older age represents a risk factor for the development of cardiovascular side effects, 28,80 while others have not. 17,70,97,98 It should be noted, however, that studies in which a positive correlation was found are those in which older patients (up to 65 years old) were included. Finally, an association of risk of CHF with age has been proposed for patients receiving anthracycline-based chemotherapy.…”
Section: Radiation Treatmentmentioning
confidence: 99%
“…Occasionally for sex-mismatched donor/recipient pairs, fluorescence in situ hybridization for X and Y chromosomes was used. 12,13 No lineage-specific engraftment analysis (e.g. T-cell chimerism) was available.…”
Section: Chimerismmentioning
confidence: 99%